ANALISIS FENOMENA BINTANG KEJORA DALAM PENENTUAN AWAL WAKTU SALAT - Firdausi; Latuconsina, Mahyuddin; Laman, Ilham (HISABUNA: Jurnal Ilmu Falak, 2023)
This research discusses the phenomenon of the Morning Star which is visible at dusk and dawn, so this research focuses on the early journey of the Isha’ prayer and Fajr prayers with the aim of 1) to know the phenomenon of the Morning Star according to science, 2) to find out the implementation of the Morning Star phenomenon in number of prayer times. This research is a library research, with a normative theology (syar’i) approach. The results obtained from this study are that the Morning Star phenomenon is the Planet Venus which appears late at night and appears late in the morning, so it is also known as the Evening Star and Morning Star. The planet Venus has a thick atmosphere and is always shrouded in clouds, making it look shiny from Earth. In addition, paying for the start of the prayer time by looking at the Morning Star can only be used to determine the start of the Isha and Fajr prayers, and can only be used at certain times. From the research conducted, it is clear that the Morning Star is visible before the time for the Isha prayer starts, as well as during the Fajr prayer. Therefore, this star can only be used as a marker for the start of the time for the Isha prayers and the Fajr prayer, not as a marker for the start of the time for the Isha prayers and the Fajr prayer. Keywords: Morning Star, Isha Prayer and Dawn, Venus